Promoting Decentralized Sustainable Energy Systems in Different Supply Scenarios: The Role of Autarky Aspiration - Ecker, Franz; Hahnel, Ulf J. J.; Spada, Hans (Frontiers in Energy Research, 2017)
The development of decentralized renewable energy systems is of crucial importance for the decarbonization of energy generation worldwide. Purchase decisions regarding innovative energy systems depend to some extent on consumers' perception of the systems' degree of autarky. We assumed that, in addition to the energetic perspective, consumers associate other non-energetic facets such as independence, autonomy, self-sufficiency or control with the concept of autarky. These psychological facets of autarky were expected to contribute to purchase decisions. In Study 1, participants (N=168) evaluated three future energy supply scenarios. The scenarios varied regarding their range of autarky (household/ neighborhood/ small town), but the individually realized degree of energetic autarky did not vary. Participants reported a higher willingness to pay in connection with a higher perceived psychological autarky for the Household Scenario. Study 1's findings were confirmed by Study 2, in which qualitative interviews (N=13) also revealed that participants favored the Household Scenario on several points. These evaluations were driven by the anticipated psychological facets of autarky, that is the subjective perception of being independent, autonomous, self-sufficient, energy secure and of control. To promote an adoption of renewable energy systems, these psychological autarky facets need to be addressed. Enabling the people to self-determine, control and secure their energy provision even in complex organizational settings in such a manner is likely to increase their acceptance and therefore foster the required social transition as a whole.